The child anxiety life interference scale for parents (CALIS-P): psychometric properties of the Spanish version - Orgilés, Mireia; Melero, Silvia; Fernández-Martínez, Iván; Espada, José Pedro; Morales, Alexandra (Current psychology (New Brunswick, N.J.), 2022)
Anxiety disorders have a negative emotional, social, family, and academic impact on children’s lives. Evaluation of childhood anxiety has focused mainly on symptomatology, and measures of anxiety life interference in children are scarce. Furthermore, collecting information about the interference of anxiety in children’s and their family’s daily functioning through multiple informants is recommended for better diagnosis and intervention. The Child Anxiety Life Interference Scale – parent version (CALIS-P) analyses life interference and impairment related to children’s anxiety both in their own daily functioning and in their parents’ lives. The current study aimed to examine the psychometric properties of the Spanish version of CALIS-P in a sample of children aged 6–8 years. Participants were 181 primary school children (45.9% girls), and data was collected through their parents, who completed assessment instruments about their children’s emotional status. Factorial structure, reliability, convergent and divergent validity of the Spanish CALIS-P were examined. Confirmatory factor analysis supported the good fit of the original three-factor model. High internal consistency was found for the total score (.91) and subscales (.75–.87), and temporal stability after 4 weeks was also satisfactory (ICC > .65). Convergent validity was examined through positive correlations between the CALIS-P and measures of anxiety symptoms (Spence Children’s Anxiety Scale [SCAS-P] and the Strengths and Difficulties Questionnaire [SDQ-P]), and divergent validity was supported by negative correlations with the Prosocial Behavior Scale of the SDQ-P. This research provides evidence of the instrument’s utility both in research and in clinical practice.